1989
DOI: 10.1101/gad.3.12b.2050
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MRF4: a new member of the muscle regulatory factor gene family.

Abstract: We have identified a rat cDNA encoding MRF4, a new member of the muscle regulatory factor gene family that includes MyoD1, myogenin, and Myf-5. MRF4 encodes a predicted 27-kD protein that contains a conserved helix-loop-helix motif, which is a common feature of this gene family. Northern analyses indicate that MRF4 is expressed solely in skeletal muscle tissue but is not detected in most embryonic muscle cell lines. Transfection of MRF4 into C3H10T1/2 fibroblasts produces stable myogenic lineages at frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
469
2
5

Year Published

1993
1993
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 732 publications
(487 citation statements)
references
References 48 publications
11
469
2
5
Order By: Relevance
“…The "down-regulation" of the genes encoding MyoD and myogenin prior to birth suggests that they are unlikely to play a direct role in the activation of genes such as MHCPB that are not expressed until the postnatal period, when myf-6 (MRF4) is the major myogenic regulatory gene expressed (Rhodes and Konieczny, 1989). This also indicates that high levels of MyoD and myogenin probably are not essential for the maintenance of contractile protein gene expression during the postnatal period.…”
Section: Discussionmentioning
confidence: 99%
“…The "down-regulation" of the genes encoding MyoD and myogenin prior to birth suggests that they are unlikely to play a direct role in the activation of genes such as MHCPB that are not expressed until the postnatal period, when myf-6 (MRF4) is the major myogenic regulatory gene expressed (Rhodes and Konieczny, 1989). This also indicates that high levels of MyoD and myogenin probably are not essential for the maintenance of contractile protein gene expression during the postnatal period.…”
Section: Discussionmentioning
confidence: 99%
“…In the set of experiments indicated, PhK-γ Luc reporter constructs were co-transfected into 3T3 cells with pEMSVscribeα2 expression plasmids that encoded one of the four members of the MyoD family of transcription factors. MyoD, myogenin, myf5 and MRF4 were provided [11,[18][19][20]. In these experiments 1.5 µg of Luc reporter plasmid and 0.5 µg of MyoD plasmid were used in the transfection mixture together with 1 µg of the pRSV-lacZ galactosidase plasmid.…”
Section: Transient Transfections and Reporter Assaysmentioning
confidence: 99%
“…The MyoD gene identified by substract cloning for myoblast specific RNA is the prototype of a family of master regulators of skeletal myogenesis which includes in vertebrates three other members namely myogenin, Myf5 and MRF4 identified subsequently [1][2][3][4][5]. All these genes encode proteins that share a highly conserved central region termed the basic/helix-loop-helix(B-HLH) domain related to the c-myc superfamily and contain sequences essential for both dimerisation and DNA binding [6].…”
Section: Introductionmentioning
confidence: 99%
“…Nucleotide sequence analysis and amino acid comparison showed that this cDNA called TMyoD encodes a polypeptide of 276 amino acids with 70% identity to the entire Xenopus MyoD protein and 92% identity within the basic and myc-like region. Results from Northern blotting showed that the corresponding transcript is expressed both in adult and embryonic skeletal musculature and in an in vitro myogenesis system, but is undetectable in cardiac and smooth muscles and in non muscle tissues.Key words: MyoD; Myogenesis; Teleost; (Satellite cell)The MyoD gene identified by substract cloning for myoblast specific RNA is the prototype of a family of master regulators of skeletal myogenesis which includes in vertebrates three other members namely myogenin, Myf5 and MRF4 identified subsequently [1][2][3][4][5]. All these genes encode proteins that share a highly conserved central region termed the basic/helix-loop-helix(B-HLH) domain related to the c-myc superfamily and contain sequences essential for both dimerisation and DNA binding [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation